A broken, O-shaped catheter during coronary angiography: Percutaneous retrieval via femoral approach using a wire-balloon technique - Kerim Esenboğa; Demet Menekşe Gerede Uludağ; Mustafa Kılıçkap; Ali Timuçin Altın (KARE Publishing, 2020)
Entrapment of equipment during coronary angiography is an uncommon but serious complication of invasive coronary procedures. Percutaneous extraction of trapped material is the accepted method of treatment. This case report is a description of the extraction of a diagnostic catheter retained as a result of collapsing into an O-shape in the right common iliac artery while trying to engage the tip of the catheter with the right coronary ostium. This rationale and unique wire-balloon method, requiring no specifically designed device, can be simply and safely performed in similar cases.